Operation and licensing of mixed cores in water cooled reactors. (International Atomic Energy Agency, 2013)
"The performance and operation of mixed cores is of interest to many nuclear power plants as new and improved fuel designs have been introduced or a different fuel vendor has been chosen to supply fuel. Such decisions have generally been driven by economic considerations or by the expectation of improved fuel performance. The design and licensing of a fuel load in a reactor core are complex undertakings, even without the additional complication of the usage of different fuel types. The issues that need to be considered include simple geometric compatibility of different fuel types, their different thermal-hydraulic characteristics and nuclear behaviour. This publication presents the outcome and the results of two meetings held on these topics and hosted by the IAEA. The meetings provided a forum to address the above mentioned issues and to review the accumulated experience and state of the art information on mixed core operation, as well as tools and techniques that are used to analyse the core operation and to demonstrate that there are no safety related issues."--Publisher's description.
"November 2013"--Title page verso.
Keywords: Nuclear reactors -- Cores -- Licenses.; Water cooled reactors.; Nuclear fuel elements -- Design and construction.; elektronické knihy; electronic books